ANALISA PERBAIKAN TOP-BOTTOM REJECTION DALAM PROSES PRODUKSI MENGGUNAKAN METODE SIX SIGMA - Clara Intan; Suhadi Suhadi; Nova Pangastuti (Smart Education, 2025)
Abstract: Primary packaging is packaging that comes into direct contact with the product. This packaging serves to protect, preserve, and package the product, as well as provide important information to customers. As the main container, this packaging comes into direct contact with the product and maintains its quality until it reaches the customer. PT XYZ is a leading primary packaging manufacturer. The company produces three different variants of its flagship product, steel drums, which generate the most revenue. The oil, lubricant, food, and chemical sectors use steel drums. A large number of defects in finished products are caused by drum body rejection and top-bottom drum rejection. From the report data of 1,166 units produced in 2024, the most rejections came from the top-bottom production process, which consists of eight phases: pressing, opening, closing, puncture 1, puncture 2, fully open drum head puncture, head coating, and other processes. The results of this study show that UCL=0.00451 and LCL=0.00247. The sigma level is determined by converting the process after the process DPMO value is known. With a value of 436, the company's sigma level is 4.83 when the DPMO value is entered into the sigma-DPMO relationship table. Keyword: quality control; six sigma; DMAIC; reject Abstrak: Kemasan primer merupakan kemasan yang bersentuhan langsung dengan produk, kemasan ini berfungsi untuk melindungi, menjaga, dan mengemas produk, serta menyediakan informasi penting bagi pelanggan. Sebagai wadah utama, kemasan ini bersentuhan langsung dengan produk dan menjaga kualitasnya hingga sampai ke pelanggan. PT XYZ, perusahaan yang bergerak di bidang produsen kemasan primer terkemuka, perusahaan tersebut memproduksi tiga varian berbeda dari produknya produk andalannya, drum baja, menghasilkan pendapatan terbesar. Sektor minyak, pelumas, makanan, dan kimia menggunakan drum baja. Jumlah cacat yang besar pada produk jadi disebabkan oleh penolakan badan drum dan penolakan atas-bawah drum. Dari data laporan sebanyak 1.166 unit yang diproduksi pada tahun 2024, penolakan terbanyak berasal dari proses produksi atas-bawah yang terdiri dari delapan fase yaitu penekanan, pembukaan, penutupan, tusukan 1, tusukan 2, tusukan kepala drum terbuka sepenuhnya, pelapisan kepala, dan proses lainnya. Hasil penelitian ini menunjukkan bahwa UCL=0,00451 dan LCL=0,00247. Tingkat sigma ditentukan dengan mengonversi proses setelah nilai DPMO proses diketahui. Dengan nilai 436, tingkat sigma perusahaan sebesar 4,83 ketika nilai DPMO dimasukkan ke dalam tabel hubungan sigma-DPMO. Kata kunci: pengendalian kualitas; Six Sigma; DMAIC; penolakan